Dynamics of an Inverting Tippe Top - Rauch-Wojciechowski, S.; Rutstam, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The existing results about inversion of a tippe top (TT) establish stability of asymptotic solutions and prove inversion by using the LaSalle theorem. Dynamical behaviour of inverting solutions has only been explored numerically and with the use of certain perturbation techniques. The aim of this paper is to provide analytical arguments showing oscillatory behaviour of TT through the use of the main equation for the TT.